The institutionalization of psychology in Lithuania: View from the prospect of the state’s 100-year anniversary - Bagdonas, Albinas (Psichologija, 2018)
Different sides of the development of psychology as a science, a teaching subject and a professional activity in Lithuania during the 100-year period are analyzed and discussed. This analysis is performed in the context of the institutionalization of the modern Lithuania. The three main premises of the development of psychology in Lithuania are revealed: the sociopolitical and economical context of state, the influence of the global field of psychology and the activities of the enthusiasts of profession. The extent of development of psychology in Lituania during the different periods of Lithuanian history of last 100 years of its existance is evaluated according to 10 criteria of recognizing the profession: 1) Social need; 2) State regulation of the profession; 3) Legislative basis of the profession; 4) Trust by society and authority; 5) Control of professional competence; 6) Being included in a classification of scienes and a scientific studies system; 7) Education (teaching and training) of the profession; 8) Professional and scientiffic communication (journals, conferences); 9) Values and professional ethics; 10) Professional self-regulation (professional NGO). The development of psychology in Lithuania can be divided in stages according to the context of the modern state’s development events: 1) Before the year 1918 (the period of arousal and enlightenment in psychological culture); 2) The years 1918–1940 (start of the institutionalization of psychology in the First Republic of Lithuania); 3) The years 1940–1944 (an empty, topsyturvy-esque or confused of social and economical life stage during the Second World War); 4) The years 1945–1988 (an unsettled stage of training and researches in psychology with stabilization after when psychologists were begun to be educated at Vilnius University in 1969); 5) The years 1989–2018 (a dissociation from the Russian academic field of psychology and an independent development with the rising ifluence of Western academic psychological influences). The names of the main enthusiasts of the institutionalization of psychology in Lithuania during the five listed stages are presented. The main persons from this list were Alfonsas Gučas (1907–1988), Jonas Vabalas-Gudaitis (1881–1955), Vladas Lazersonas (1889–1945) and Juvencijus Lapė (1925–1911). The main conclusion of paper is that psychology in Lithuania, during the 100-year period, was developed according to all 10 criteria; it was reasonably adapted to the national state culture and infrastructure. In other words, at the present time, we can speak and write not only about the development of psychology in Lithuania but about a Lithuanian psychology – a nationally indigenized profession. Eleven features of indeginized psychology are also listed.